The Influence of “Ubrug” Sociodrama Technique toward Students Self-Efficacy - Permatasari, Siska; Rahmawati; Dalimunthe, Raudah Zaimah (Journal of Family Sciences, 2020)
The study's purpose is to know the effects of the 'ubrug' sociodrama technique 'on a student's self-efficacy and the effectiveness or failure of a given technique. This type of research is a pre-experimental study using one group pre-post test design. The population taken as many as 112 students with the characteristics of class IX students (a, b, and c), aged 14-16 years, have low self-efficacy with a lack of self-confidence and slightly more closed behavior, are willing to take the time to fill out the questionnaire given, and students must be committed to the "Ubrug" sociodrama treatment. Obtained a sample of 15 students with a purposive sampling technique. The data collection method uses a self-efficacy questionnaire consisting of 34 statement items with a reliability value (count) of 0.896. The results of giving a post-test prove that there is an increase in the results obtained by students significantly. It can be concluded that the Sociodrama Technique "Ubrug" can increase the self-efficacy of IX grade students at SMPN 5 Kota Serang.